The cool bean - John, Jory (Harper, an imprint of HarperCollinsPublishers, 2019)
Everyone knows the cool beans. They're sooooo cool. And then there's the uncool has-bean ... Always on the sidelines, one bean unsuccessfully tries everything he can to fit in with the crowd--until one day the cool beans show him how it's done.